Industrial egg residue as a calcium source in broiler feed: digestibility and growth performance - Novack C.* (2023)
© 2023, Academia Brasileira de Ciencias. All rights reserved.Industrial egg residue (IER) possesses substantial concentrations of calcium and crude protein. The objective of this study was to measure the digestibility and performance of broilers when IER was added to the feed. Four treatments were tested, which caused increasing replacement of calcitic limestone by IER (0, 35, 70 and 100%) during a 42-day production cycle. First, total bird excreta were collected from broilers with and without IER, and we determined dry matter digestibility, apparent metabolizable energy (AME), calcium, and nitrogen retention. The IER presented 7.5% of crude protein, 31% of calcium, 209 kcal/kg of AME and the digestibility coefficients for dry matter, crude protein, and calcium were calculated at 83.95%, 86.20%, and 67%, respectively. After the digestibility test, the effects of IER on performance, carcass and meat yield were evaluated. No significant differences between the treatments were found in terms of performance (weight gain, feed conversion, consumption, and mortality), and no differences were found in terms of carcass or meat yield. A linear decrease in the percentage of abdominal fat was observed with increasing inclusion of IER in feed. These findings suggest that IER can totally replace limestone (calcium carbonate) in broiler diets.